Primary Hydatid of Adductor Muscle of Thigh: A Rare Entity - Singh, Punyapratap; Pandey, Somshankar; Ahirwar, Vrishbhan (Nepalese Journal of Radiology, 2019)
Primary Muscle involvement of hydatid disease is a rare entity. Radiological diagnosis can be difficult at times as it mimics soft tissue tumor. Multiple imaging studies are available to detect it preoperatively. We hereby report an in a male patient with hydatid disease of adductor group of muscles of right thigh diagnosed on ultrasound followed by MRI and confirmed on surgery and histopathological examination.